High resolution tephrostratigraphy, fossil record and age of Carboniferous-Permian glaciomarine mudstones within the Dwyka Group of southern Namibia. - Bangert, Berthold; Stollhofen, Harald; Geiger, Markus; Lorenz, Volker (Communications - Geological Survey of Namibia, 2000)
The Carboniferous Dwyka Group in southern Namibia can be subdivided into four upward-fining deglaciation sequences, each capped by relatively fine-grained glaciolacustrine or glaciomarine deposits. The uppermost part of the second deglaciation sequence comprises a thick fossiliferous mudstone unit, referred to as the ”Ganigobis Shale Member”. An abundance of marine macro- and ichnofossils as well as extrabasinally derived ashfall tuff horizons characterise the mudstones and provide the basis for an integrated high-resolution biostratigraphic and tephrostratigraphic framework. The marine body and trace fossils record the extent of the first of a series of marine incursions into the disintegrating Gondwanan interior as early as the Carboniferous. Juvenile magmatic zircons separated from tuff horizons interbedded with the Ganigobis Shale Member yield SHRIMP-ages of 300-302 Ma. This dates the uppermost part of the second deglaciation sequence in southern Namibia to the late Carboniferous (Gzelian) and provides a minimum age for the onset of Karoo-equivalent marine deposition prior to the much more widespread Eurydesma transgression.
UnivIS-Import:2015-03-09:Pub.2000.nat.dgeo.IGM.LG.highre